Theoretical study of the circular dichroism spectroscopy of proteins - Li, Zhuo (2018)
Circular dichroism (CD) spectroscopy is an important technique in studying protein structure, especially for protein secondary structures and conformational changes during biological processes. A fully quantitative theory of the relationship between protein conformation and optical spectroscopy would facilitate deeper interpretation and insight into biophysical and simulation studies of protein dynamics and folding. Vibrational structure in the electronic CD spectra of proteins is an important source of information on protein conformation and can be exploited to study structure and folding. We employ the state-averaged complete active space (CAS) method to calculate the ab initio electronic ground and excited states of N-methylacetamide (NMA), toluene, p-cresol and 3-methylindole (3-MI), which represent chromophores that are significant in the CD spectroscopy of proteins in the far- and near-ultraviolet (UV) regions. The results of these calculations are used to incorporate vibronic levels of the excited states into first principles calculations of CD using an exciton approach.